PENGARUH TEKANAN KEMPA DAN KONSENTRASI PEREKAT TERHADAP SIFAT BIOBRIKET DARI LIMBAH TEMPURUNG SAWIT - Purwanto, Djoko; Purbaningtyas, Retno Utami; Suryani, Santy Diah (Jurnal Riset Industri Hasil Hutan, 2015)
Palm shell waste has not been used optimally. Utilization can be as fuel in the form of biobriquette. The purpose of this research studied the effects of pressure hydraulic and adhesive concentration on biobriquette properties. Research includes palm shell crushed, screened with fineness 7 mesh, mixed with amylum adhesive solution 2.5% and 5%. Printed in diameter of 3 cm and a height of 7 cm. The emphasis with the pressure of 3 tons, 5 tons and 7 tons. Biobriqutte dried naturally. Quality analysis with refers to the National Standardization Agency (1994). Results pressure 3 tons and adhesive concentration of 5% produces the best with sulfur levels of negative value and calorific 4442.78 cal / g and qualify for household fuels. Treatment interactions pressure and concentration of adhesive very significant effect on moisture, ash, carbon, volatile matter content, density and compressive strengtth biobriqutte.Keywords: Â palm shell,Â  consentration of adhesive, pressure hydraulics, biobriquette